2011
DOI: 10.1007/s00018-011-0728-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha T-catenin (CTNNA3): a gene in the hand is worth two in the nest

Abstract: Alpha-T-Catenin (CTNNA3) is a key protein of the adherens junctional complex in epithelial cells playing a crucial role in cellular adherence. What makes this gene particularly interesting is that it is located within a common fragile site, is epigenetically regulated, is transcribed through multiple promoters, and generates a variety of alternate transcripts. Finally, CTNNA3 has a nested gene (LRTMM3) embedded within its genomic context transcribed in the opposite direction. Apart from the complexity of its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…It is transcribed using multiple promoters, which produce alternate transcripts (31). The importance of CTNNA3 in maintaining cell-cell adhesion may play a role in allergy.…”
Section: Discussionmentioning
confidence: 99%
“…It is transcribed using multiple promoters, which produce alternate transcripts (31). The importance of CTNNA3 in maintaining cell-cell adhesion may play a role in allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three of the genes are located within introns of genes encoding different α-Catenin proteins [known to facilitate interactions between cadherins and actin fi laments, Pokutta et al ( 2008 )], and in all cases the LRRTM genes are transcribed in the opposite direction as the CTNN genes, suggesting coevolution of the of two families; LRRTM1 is located within CTNNA2 , LRRTM2 is located within CTNNA1 , and LRRTM3 is located within CTNNA3 (Lauren et al 2003 ); [see also Smith et al ( 2011b )]. Recently it was demonstrated that CTNNA1 and CTNNA2 contain alternative bidirectional promoters that are used for the transcription of CTNNA1 and CTNNA2 as well as LRRTM2 and LRRTM1 , respectively.…”
Section: Genes and Proteinsmentioning
confidence: 96%
“…the heart, it can be found at AJs (Dejana et al 2009;Li and Radice 2010). The mammalian α-catenin family consists of three members: αE-catenin, which is ubiqioutisly expressed, αN-catenin, which is exclusively found in the brain, and αT-catenin (Smith et al 2011;Maiden and Hardin 2011). Lastly, several members of the p120 subfamily of armadillo proteins, such as δ-catenin at synapses, bind classical cadherins and are found at AJs (Carnahan et al 2011;McCrea and Park 2007;Pieters et al 2012).…”
Section: )mentioning
confidence: 97%